Joyful and Meaningful Learning of Integers through the Traditional Game Mpa’a Geta to Promote Students’ Motivation in Learning Mathematics - Mardiah; Astuti (Samudra Publisher, 2025)
This study aims to describe the implementation of the traditional game Mpa’a Geta in teaching integer multiplication and to examine its contribution to students’ conceptual understanding and motivation in learning mathematics. The research employed a descriptive qualitative approach involving 21 seventh-grade students during a 2 × 45-minute learning session. Data were collected through classroom observation, documentation, student responses, and teacher reflection, and were analyzed using thematic techniques. The findings indicate that the Mpa’a Geta game creates a joyful and meaningful learning environment, enhances student engagement, and facilitates conceptual understanding of integer multiplication through concrete activities. Student responses revealed that the game helped them better grasp the rules of positive and negative signs, while teacher reflections confirmed that the activity effectively supported the learning objectives. The game also increased students’ intrinsic motivation due to its interactive, collaborative, and culturally relevant nature. Therefore, the traditional game Mpa’a Geta holds strong potential as an alternative instructional strategy for teaching fundamental mathematical concepts in a contextual and enjoyable manner.